(untitled) (Journal of Ideas in Health, 2024)
Background: The implementation of the Integrated Management of Childhood Illness (IMCI) program has led to enhancement in outcomes for many treatable childhood diseases. This study aims to assess how implementing IMCI affects child mortality and morbidity in Iraq. Methods: A cross-sectional study spanning from January to December 2021 was carried out at primary healthcare centers (PHCCs) with IMCI units in Baghdad, Iraq. Using a lottery sampling method, 40 PHCCs were randomly chosen from a total of 235 centers across both sides of the city. A universal sampling technique was adopted to select all children attending these PHCCs regularly. With a p-value below 5%, multiple logistic regression analyses were performed to identify the significant independent predictors at a 95% confidence interval. Results: The majority of caregivers were mothers (97.8%), aged 20 to 30 years (75.8%), and housewives (59.2%). Sixty percent of children (6 to 35 months) had normal anthropometric measurements. Bottle feeding was common (44.2%), and most children had a normal neonatal history (82.9%). In bivariate analysis, the severity of illness, severe cases of diarrhea, and acute respiratory infection (ARI) showed significant associations with worsened or not improved outcomes (χ2 = 18.900, p < 0.001; χ2 = 6.265, p= 0.016; and χ2 = 7.549, p= 0.003, respectively). However, multiple logistic regression analysis indicated that mild and moderate illness severity (OR = 10.634, 95% CI: 6.985 to 16.192, p < 0.001), strict breastfeeding (OR = 3.307, 95% CI: 1.703 to 6.421, p < 0.001), and completing treatment at home (OR = 6.190, 95% CI: 4.115 to 9.311, p < 0.001) significantly improved outcomes through IMCI services. Conclusion: Severe illness, especially in diarrhea and ARI, correlates with poorer outcomes. Conversely, exclusive breastfeeding, prompt medical attention within a day of illness onset, and completing home treatment are associated with improved outcomes.